Dampak Alih Fungsi Lahan dan Curah Hujan terhadap Banjir di Kota Pekalongan, Jawa Tengah - Gardena Smoro Laksmi (Seminar Nasional Lahan Suboptimal, 2020)
Laksmi GS. 2020. Impact of land use change and rainfall on flooding in Pekalongan city, Central Java. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pekalongan City is located on the northern coast of Central Java Province which connects Jakarta, Semarang, and Surabaya. Located on the main route to Java Island, Pekalongan City has strategic economic potential, especially in the industrial sector. This condition caused Pekalongan City to become the area with the highest demographic urbanization value in Central Java in 2006 and led to changes in land cover. Land-use change will have negative impacts if uncontrolled like the reduction in catchment areas, especially if the rainfall is high. This study is a literature study that contains the effect of land-use change and rainfall on flooding in Pekalongan City. Data and information come from various journals related to floods in Pekalongan City. This study aims to analyze the impact of land use change and rainfall on waterways in Pekalongan City. Changes in land cover and rainfall have a strong correlation. The reduced water catchment area causes the increase of flood index. Pekalongan City was categorized as a city that was not prone to flooding in 2011, but in 2017, all villages in North Pekalongan Regency were flooded with an area of 1,249,420 hectares.